Relationship Between Head Teacher Effectiveness and School Performance at Secondary Level - Dr. Saima Kayani; Sara Abid; Malik Zulqarnain Sadiqi, (Dialogue Social Science Review (DSSR), 2025)
This study conducted to find out the Relationship between Head teacher Effectiveness and School Performance at Secondary level in Kotli AJ&K. The purpose of this research is to identify head teachers effectiveness at secondary school level. To find out performance of schools at secondary level. To examine the relationship between head teachers effectiveness and school performance at secondary level. The population of the study consisted of all the government secondary school in District Kotli. Random sampling technique used for the selection of sample of Teachers (109). The current study was quantitative in nature. Descriptive research used to conduct the study and survey method conducted for data collection. A five-point Likert scale questionnaire used as a tool in this study. The questionnaire validated from five expert of the department of education. University of Kotli Azad Jammu and Kashmir. The researcher personally visited the Government schools of Kotli Azad Jammu and Kashmir and collected the data. Statistical package for Social Science software (SPSS) used for the analysis of data. The researcher applied frequency, percentage, mean and standard deviation for the analysis of data. The researcher also applied correlation analysis. It is concluded that teachers feel when their energy is low and take a short break to boosts themselves. They also admit that if they make mistakes then they are ready for apologize. Furthermore, teachers think clearly before expressing their opinions about related information and also let go sadness anger, or fears from the past and move on. It is recommended that school administrators may adopt a management approach in which all teachers can express their opinions and suggestions clearly, and the diversities of individuals are seen as a wealth.